Collaborative Roles of Teachers and Parents in Supporting Students with Special Needs: Peran Kolaboratif Guru dan Orang Tua dalam Mendukung Siswa Berkebutuhan Khusus - Mirna, Mirna; Chamidah, Atien Nur (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Inclusive education aims to provide equitable learning opportunities for all children, including those with special needs. Specific background: In Indonesia, the implementation of inclusive education remains challenging due to limited teacher expertise, parental understanding, and school resources. Knowledge gap: Few studies have explored how teachers and parents collaborate effectively to support special needs students in rural primary schools. Aims: This research analyzes how educators and parents work together to optimize the learning process for students with special needs at SDN 002 Sangkulirang. Results: Findings reveal that teachers act as adaptive facilitators who employ individualized strategies and concrete media, while parents provide consistent home supervision and direct participation at school. Communication that is open, flexible, and continuous strengthens this partnership. However, challenges persist, including teachers’ limited knowledge, insufficient professional support staff, and parents’ lack of understanding regarding their children’s specific conditions. Novelty: This study highlights the integrated and contextual forms of teacher–parent collaboration in rural inclusive schools. Implications: Strengthening teacher training, parental education, and structured school–home collaboration are crucial to creating a sustainable inclusive learning environment. Highlights Teachers and parents share adaptive and responsive roles in supporting special needs students. Effective collaboration depends on open communication and consistent home–school coordination. Limited knowledge and resources remain barriers to inclusive learning practices. Keywords Teacher Collaboration, Parental Involvement, Inclusive Education, Special Needs Students, School Partnership